Leading the Borderline: Transformational Leadership and Performance Reform in Immigration Bureaucracy - Harahap, Morina; Wibisono, Chablullah; Satriawan, Bambang; Dewi, Nolla Puspita (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates the transformation of employee performance within Indonesia’s immigration sector, focusing on the Riau Islands Province, Indonesia. It examines how transformational leadership, organizational culture, and innovation interact within bureaucratic settings to inform evolving models of public-sector performance. A mixed-method Sequential Explanatory Design is employed, integrating structural equation modelling (LISREL; n = 247) with qualitative analysis via NVivo 12 Plus. Results reveal that transformational leadership and digital innovation exert a significant positive influence on employee performance, while motivational and trust-related factors enhance service effectiveness. These findings contribute to the evolving discourse on leadership and performance in high-stakes bureaucratic contexts, particularly within border governance. The study underscores the critical role of leadership in driving adaptive capabilities and cultural alignment within complex government institutions. For policy makers and public-sector managers, the results offer actionable insight into developing more responsive, accountable, and innovation-ready immigration services in peripheral and strategic regions.